Peningkatan Kemampuan Mengenal Angka dengan Menggunakan Metode Snowball Throwing bagi Anak - Muntari, Sri (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2018)
This study aims to determine the ability to recognize the numbers of students in Group A TK Widya Tama Cabak and the use of the snowball throwing method can improve the ability to recognize the numbers of students in Group A TK Widya Tama Cabak Academic Year 2016/2017. The subjects studied were 31 students of group A TK Widya Tama Cabak. Data collection techniques using observation, interview, and documentation techniques. The data analysis technique uses descriptive qualitative and comparative. The research procedure consists of two cycles, namely: cycle I and cycle II, with each of the four stages of each cycle, namely: (1) planning the action (planning), (2) implementing the action (acting), (3) observing ( observing), and (4) reflection (reflecting). The results of the study concluded that: (1) Ability to recognize the numbers of students in Group A Widya Tama Cabak Kindergarten in the 2016/2017 Academic Year before the action was taken, namely at the pre-cycle level was still low. The ability to recognize the number of children included in the BSB and BSH categories in the pre-cycle was only 10 children (32.26%). (2) The use of the snowball throwing method can increase the ability to recognize the numbers of students in Group A TK Widya Tama Cabak for the 2016/2017 Academic Year. This is evidenced from: (a) Increasing the ability to recognize the number of children included in the BSB and BSH categories starting from the pre cycle, cycle I to cycle II, namely: the new pre cycle of 32.26%, the first cycle becomes 64.52% and the cycle II to be 90.32%. (b) Increasing the average value of the ability to recognize the number of children starting from the pre-cycle, the first cycle to the second cycle, namely: pre-cycle of 11.61 which included the Emerging (MM) category, cycle I increased to 13.16 which included the category Developing according to Expectations (BSH) and the second cycle the score increased again to 15.39 and included the Expectation Development Expectation (BSH) category.